2003
DOI: 10.1073/pnas.1432927100
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for association of schizophrenia with genetic variation in the 8p21.3 gene, PPP3CC , encoding the calcineurin gamma subunit

Abstract: Schizophrenia is a severe psychiatric disorder characterized by a complex mode of inheritance. Forebrain-specific CNB knockout mice display a spectrum of behavioral abnormalities related to altered behaviors observed in schizophrenia patients. To examine whether calcineurin dysfunction is involved in schizophrenia etiology, we undertook studies of an initial subset of calcineurinrelated genes, prioritizing ones that map to loci previously implicated in schizophrenia by linkage studies. Transmission disequilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 229 publications
(154 citation statements)
references
References 55 publications
(48 reference statements)
9
143
0
1
Order By: Relevance
“…Comparing our SNP markers with the significant SNPs reported by Gerber's et al, 7 we had a wider range (from the promoter region to intron 12) of coverage in PPP3CC gene than did Gerber's SNPs (from exon 1 to intron 4). Distal to exon 1, the SNP of rs2272080 (primer ID 6577) showed statistical Table 2.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…Comparing our SNP markers with the significant SNPs reported by Gerber's et al, 7 we had a wider range (from the promoter region to intron 12) of coverage in PPP3CC gene than did Gerber's SNPs (from exon 1 to intron 4). Distal to exon 1, the SNP of rs2272080 (primer ID 6577) showed statistical Table 2.…”
Section: Discussionsupporting
confidence: 47%
“…The 10 SNP markers used in this study covered a wide-enough genomic regions, ranging from the SLC39A14 gene close to the PPP3CC promoter region to the promoter region of the next SCAM-1 gene, with an average SNP marker distance of about 12.9 kb. One SNP, CCS3 (equal to primer ID 6555), was also used by Gerber et al 7 Significant associations had been demonstrated between SNP CCS3 and schizophrenia in the latter investigation (P = 0.041) but not in the present study (P = 0.33). Of the five PPP3CC SNPs screened by Gerber et al, 7 which covered the genomic regions from exon 1 (rs1049437) to intron 4 (rs2461491), their most significant SNP locus is at the intron 1 of CC21 (P = 0.038) close to our significant SNP 6577.…”
Section: Discussionsupporting
confidence: 40%
See 3 more Smart Citations